Landscapes: Ways of Imagining the World - Winchester, Hilary (Institutional Knowledge at Singapore Management University, 2003)
An analysis of the meaning of cultural landscapes, this book delves into the layers of meaning that are invested in ordinary as well as spectacular landscapes.